2018
DOI: 10.1101/333161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The maternal hormone in the male brain: sexually dimorphic distribution of prolactin signalling in the mouse brain

Abstract: Research of the central actions of prolactin is virtually restricted to females, but this hormone has also documented roles in male physiology and behaviour. Here, we provide the first description of the pattern of prolactin-derived signalling in the male mouse brain, employing the immunostaining of phosphorylated signal transducer and activator of transcription 5 (pSTAT5) after exogenous prolactin administration. Next, we explore possible sexually dimorphic differences by comparing pSTAT5 immunoreactivity in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
3
1
Order By: Relevance
“…Expression of the Prlr and of pSTAT5 in the MPOA has been reported to be sexdependent [6,9]. Nonetheless, our investigations detected little difference in the proportion of prolactin-responsive cells in virgin males, females or lactating females.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Expression of the Prlr and of pSTAT5 in the MPOA has been reported to be sexdependent [6,9]. Nonetheless, our investigations detected little difference in the proportion of prolactin-responsive cells in virgin males, females or lactating females.…”
Section: Discussioncontrasting
confidence: 52%
“…Binding of prolactin to its receptor exerts co-ordinated effects on gene transcription dependent on phosphorylation of the STAT5 transcription factor. Utilising immunohistochemical labelling of phosphorylated STAT5 (pSTAT5) has therefore been an effective method of mapping prolactin-responsive cells [7][8][9][10]. In the central nervous system (CNS), prolactin-induced pSTAT5 is widely distributed in forebrain and brainstem areas [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence indicating that sexual steroids (late-pregnancy progesterone withdrawal and estradiol surge) plus placental lactogens (late pregnancy) and/or hypophysial prolactin (postpartum) (see Bridges, 2020 ) are needed to induce fully motivated maternal behaviors. Recent work has shown that during pregnancy and postpartum, lactogens are able to influence the SBN nodes ( Salais-López et al., 2017 , 2021 ) that also concentrate estradiol-sensitive cells ( Mitra et al., 2003 ; Simerly et al., 1990 ), whereas the nuclei composing the motivational brain circuitry do not express prolactin receptors ( Kokay et al., 2018 ; Salais-López et al., 2018 ) or few estrogen receptors ( Mitra et al., 2003 ; Simerly et al., 1990 ). Therefore, the influence of pregnancy hormones on motivation must be indirect, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin‐responsive neurons are abundant in the hypothalamus with discrete distribution in specific brain nuclei related to food intake, energy expenditure, and metabolism, such as the arcuate nucleus (ARN), ventromedial nucleus (VMN), and dorsomedial nucleus (DMN), among others. Indeed, the hypothalamus is the cornerstone of food intake regulation and regionally organized nuclei constitute intricate pieces that help to build a coordinated response to metabolic needs, perceived neurally or hormonally.…”
Section: Introductionmentioning
confidence: 99%